Moonlighting, Harm? : Student Perception of the Effects of Moonlighting, Achievement Motivation on Lecturer Performance - Hartina Fattah; Andi Batari Citta (Journal of International Conference Proceedings (JICP), 2018)
This study aims to determine students 'perceptions of the term moonlighting lecturers and find out the effect of moonlighting on lecturers' performance which is mediated by achievement motivation. This study uses quantitative methods with path analysis based on data from 145 respondents consisting of lecturers and students at private universities in Jeneponto Regency. The results of the study showed that students perceive moonlighting as a natural thing for lecturers to do as an alternative to meet the needs of lecturers. The findings indicate that moonlighting has a significantly positive indirect effect which is mediated by lecturer achievement motivation on the performance of lecturers. Keywords: moonlighting, achievement motivation, lecturer performance, student perceptions.